PARTISIPASI MASYARAKAT DALAM MENDUKUNG KEBERHASILAN PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH DI SMP NEGERI 1 PALU - Fatmawati Lahama; Asep Mahpuds; Jamaluddin Jamaluddin (Katalogis, 2018)
This study aims to analyze: (1) form of community participation, (2) the mechanism of community participation and school efforts to increase community participation in the implementation of school-based management in SMP Negeri 1 Palu. The research method used is a survey method with the approach used is qualitative descriptive. Sampling is done by simple random technique. Data collection metho in the researcher are, interviews and questionnaires. The data obtained from the results of interviews, observations, document recordings, complete field notes are then made data reduction then followed by data presentation then a temporary conclusion is formulated. The results showed that community participation in the implementation of school-based management in SMP Negeri 1 Palu were: (1) participation in the form of taking decisions, participation in the form of planning, implementing and evaluating school activities, namely people involved in meetings between giving input/suggestions and criticisms of planning the school program then participates in the implementation and evaluation of activities (2) Mechanism of community participation in supporting the success of school-based management in SMP Negeri 1 Palu, namely decision making, implementation that mobilizes funding resources, administrative activities, coordination and elaboration of programs, benefit taking, and evaluation. (3) Efforts to increase community participation are holding friendships with parents, calling parents if there are difficulties experienced by the school, establishing intentional communication, and holding consultations with parents.